Numerical study on the pipe containing multiple aligned axial cracks - Mohamad Zikril Hakim, Md Saleh (2013)
Failures due to the multiple cracks become a major concern in the pipeline industry and also in maintaining the pipeline integrity. The predictions of pipeline burst pressure in the early stage are very important in order to provide assessment for future inspection. The effects of the multiple aligned axial cracks on burst pressure of material Grade B was studied through an experimental and numerical simulation. The objectives of this research are to investigate the effects of multiple aligned axial cracks towards the burst pressure. This research focuses on two types of analysis which is experimental and simulations by using material Grade B pipe with outer diameter of 60.5mm, 600mm in length and thickness of 4mm. The burst test is done by applying internal pressure of hydraulic oil continuously at the pipe with artificially machined cracks until the pipe burst. MSC Marc Patran 2008r1 is used as a pre-processor and a solver in the analysis of material Grade B. A half of the pipe was modeled by considering the symmetrical conditions using the same parameter with a pipe that used in the burst test. In both analyses of experiment and simulation, the stress and strain are used as criteria for predicting the failure of the pipe. The result shows that as the length of the cracks increase, the burst pressure is decreased. The assessment method in predicting the burst pressure such as ASME B31G, Modified ASME B31G and DNV-RP-F-101 used as the comparison with the result taken from the analysis.